EFFECT OF THE DRUG Miopets® ON BODY WEIGHT AND CLINICAL AND PHYSIOLOGICAL INDICATORS OF HEALTHY PUPPIES - Yunusov H. B.; Niyozov H.B.; Eshkuvatov Kh.Kh.; S.B. Abdiev; Pardaeva Sh. A.; B. Kokilov; A. Ruziev (The Conference Hub, 2025)
This article describes that in the treatment of dog puppies suffering from exhaustion and hypotrophy, along with antiparasitic agents and symptomatic therapy, with parenteral administration of gamma globulin at a rate of 1 ml per 1 kg of live weight, as well as with the introduction of the immunomodulator MioPets® intramuscularly: for the first time - 1 ml, repeated - after 5 days 1 ml, by the 20th day, the animals showed positive changes - improved mobility, growth and development. By the end of the experiment, the body weight of dogs in the experimental group was 4.400 ± 0.14 kg, which is on average 1600 g more than at the beginning and 700 g more than in the control group.
Keywords: hypotrophy, gamma globulin, parenteral, diarrhea, symptomatic therapy, drugs, chewing reflex, mucous membranes, intoxication, respiratory and digestive systems, nervous system, Miopets®.Актуальность темы.